Exploring anomeric glycosylation of phosphoric acid: Optimisation and scope for non-native substrates. (February 2020) - Beswick, Laura; Ahmadipour, Sanaz; Hofman, Gert-Jan; Wootton, Hannah; Dimitriou, Eleni; Reynisson, Jóhannes; Field, Robert A.; Linclau, Bruno; Miller, Gavin J.
Graphical abstract: Image 1 Highlights: Glycosyl 1-phosphate chemical synthesis. Anomeric phosphorylation of acetylated precursors. Evaluation of glycosylation methodology to access native and modified glycosyl 1-phosphates.